Incident Atrial Fibrillation, Dementia and the Role of Anticoagulation: A Population-Based Cohort Study - Field, Thalia S.; Weijs, Bob; Curcio, Antonio; Giustozzi, Michela; Sudikas, Saulius; Katholing, Anja; Wallenhorst, Christopher; Weitz, Jeffrey I.; Cohen, Alexander T.; Martinez, Carlos (Thrombosis and Haemostasis, 2019)
Introduction Atrial fibrillation (AF) is associated with dementia. Anticoagulation may modify this relationship, but it is unclear if this is due to stroke reduction alone.Methods Age- and sex-matched individuals from the U.K. Clinical Practice Research Datalink (2008–2016) with and without an incident diagnosis of AF were followed for a new dementia diagnosis. We estimated adjusted hazard ratios (aHRs) for incident dementia diagnosis in the AF cohort, overall and stratified by anticoagulation status, using the matched non-AF cohorts as reference. We performed a sensitivity analysis excluding individuals with stroke/transient ischaemic attack (TIA) before the observation period.Results Over 193,082 person-years (mean follow-up 25.7 ± 0.1 months), 347/15,276 AF (2.3%) and 1,085/76,096 non-AF (1.4%) were newly diagnosed with dementia (aHR, 1.31, 95% confidence interval, 1.15–1.49). The AF group had more co-morbidity and higher rates of dementia, both with and without anticoagulation, than non-AF. When those with history of stroke/ TIA before the observation period were excluded and those with incident stroke/TIA during the observation period were censored, AF individuals not on anticoagulation had significantly higher rates of dementia compared with non-AF, aHR 1.30 (1.06–1.58).Conclusion Our findings support the hypothesis that AF is a distinct risk factor for dementia, independent of stroke/TIA and other vascular risk factors. In those without stroke/TIA, risk of dementia is increased only in those who are not on anticoagulation, suggesting anticoagulation is protective presumably through reduction of sub-clinical embolic events. Further prospective research is needed to better ascertain the role of anticoagulation amongst targeted therapeutic strategies to reduce cognitive decline in AF.
Keywords: dementia; atrial fibrillation; stroke; TIA; anticoagulation; risk factors; population study